FACTORS AFFECTING THE GROWTH OF MUDHARABAH DEPOSITS IN ISLAMIC BANKS IN INDONESIA - Sasmita Purnamasari; Unggul Purwohedi; Tri Hesti Utaminingtyas (Transpublika Publisher, 2024)
This study examines the factors influencing the growth of mudharabah deposits in Islamic banks in Indonesia during the period of 2012-2020. The data used in this research is secondary data in the form of financial reports from registered and active Islamic Commercial Banks (BUS) under the supervision of the Financial Services Authority (OJK). The variables tested include both dependent and independent variables. Mudharabah deposits (DPS) are used as the dependent variable, while the interest rate (ITS), inflation rate (IFL), and Finance to Deposit Ratio (FDR) are the independent variables. Data processing in this study is conducted using Microsoft Excel, Eviews 9 program, and multiple linear regression analysis method for hypothesis testing. The findings of this research indicate that the inflation rate (IFL) has a significant impact on the growth of mudharabah deposits, while the interest rate (ITS) and Finance to Deposit Ratio (FDR) do not have a significant impact on the growth of mudharabah deposits.